Create With Oil Palm Slipes To Become Economic Value Products For The Village Of Kampung Baru Bilah Barat, Labuhanbatu - Nila Ramadayanti; Pristiyono Pristiyono; Abdul Halim (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Labuhanbatu Regency is famous for its beautiful and abundant natural resource potential. However, this potential is not matched by the creativity of the community in managing it, on the contrary, there are several obstacles that arise because the community is still working individually in utilizing the potential of these raw materials. Efforts that can overcome these problems are to provide knowledge and information to the public about the economy and entrepreneurship through empowerment. Empowerment is a process and a goal, where empowerment is very supportive of the family economy, one of which is the empowerment of the stick craft business. This service aims to find out the benefits of palm leaf buds being a unique product and having a selling value in the market that is able to open up job opportunities for people who do not have an income. The methods used are field surveys, counseling/training, practice and mentoring, and evaluation of activities. The results achieved were the formation of a Partner Group, Counseling on methods/how to make sticks, training on making sticks, and providing assistance to partner groups.